2018
DOI: 10.1177/0891988718807973
|View full text |Cite
|
Sign up to set email alerts
|

What About the Role of Virtual Reality in Parkinson Disease’s Cognitive Rehabilitation? Preliminary Findings From a Randomized Clinical Trial

Abstract: Background: The purpose of this study is to evaluate the effects of a virtual reality training with BTS Nirvana (BTS-N) system in the cognitive and behavioral recovery in patients with Parkinson disease (PD). The BTS-N is a semi-immersive therapy system used for motor and cognitive rehabilitation of patients with neurological diseases, by creating virtual scenarios with which the patient may interact. Methods: We enrolled 20 patients with PD undergoing neurorehabilitation. All the patients were randomized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 32 publications
0
69
1
6
Order By: Relevance
“…Previous studies indicated VR-based training benefits on balance (Lee et al, 2015;Liao et al, 2015;Wang et al, 2019), executive, and visuospatial (Maggio et al, 2018) abilities of participants with PD. Nevertheless, the effects on gait velocity and distance are less evident (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated VR-based training benefits on balance (Lee et al, 2015;Liao et al, 2015;Wang et al, 2019), executive, and visuospatial (Maggio et al, 2018) abilities of participants with PD. Nevertheless, the effects on gait velocity and distance are less evident (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the first point, our case-report, consistently with the literature data we reviewed here, suggests that VR could be a valuable methodology to support rehabilitation, as it allows obtaining positive functional motor and cognitive outcomes [ 13 , 14 , 48 , 56 ]. VR is the multisensory and interactive simulation of ecological scenarios, generally presented in a three-dimensional way, with which the patient can interact [ 15 , 58 , 59 , 60 , 61 ]. The VR devices use specific software with input-output peripherals that make the experience complex and engaging, promoting the improvement of the bodily functions of patients with motor/cognitive disabilities, as well as their well-being and participation [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients exhibited significant improvements on the Montreal Cognitive Assessment (MoCA) and IADL after a 3-week VRbased cognitive and physical training: interestingly, after the VR intervention, functional near-infrared spectroscopy (NIRS) revealed decreased brain activation of the prefrontal areas as a result of increased neural efficiency during the training (53). Overall, several studies have highlighted the potential of VR in memory (54-57) and executive functions rehabilitation (58)(59)(60)(61). In particular, it has been shown that the multisensory stimulation has a positive impact on both the sense of presence and memory functioning (62).…”
Section: Virtual Reality In Rehabilitationmentioning
confidence: 99%